Pemberdayaan Kerta Desa Anturan dalam Menyelesaikan Sengketa Tanah Untuk Investasi Pariwisata - I Wayan Wesna Astara; I Ketut Widia; Simon Nahak; I Wayan Rideng; Putu Ayu Sriasih Wesna; Ni Made Mahendrawati (Postgraduated Community Service Journal, 2020)
Anturan Village, which is still included in the tourist area of North Bali, has enormous potential to be developed into an adat village-based tourist destination. This village, has a unique culture, religion and customs. The potential of the Anturan traditional village in particular has Kerta Desa a kind of traditional court that can reconcile civil disputes, in the indigenous Anturan community, especially those who are Hindu. This means that prior to the enactment of Indigenous Village Law No. 4 of 2019 concerning Indigenous Villages which obliged to form a Kerta Desa, the Anturan traditional village already had a Kerta Desa. The problem arises that, even though the Kerta Desa has authority in peace in adat villages based on adat law by making decisions in accordance with awig-awig and / perarem. In the Empowerment of Anturan Indigenous Village Empowerment there are problems namely: (1) legal issues related to tourism activities in Anturan Village cannot be comprehensively solved. (2) The form of Kerta Desa's relationship with Bendesa adat and community leaders in resolving tourism cases has not been synergistic so that the law can mean coexistence. (3) There is no Kerta Desa Empowerment model, in the context of state law enforcement and Balinese customary law. (4) The absence of kerta desa in tourism law enforcement is in accordance with the interests of the local community. Solution offered: (1) Existence of Policy Study on Empowerment of Village-based Tourism Village that involves the kerta desa in handling cases of traditional village land and land in the form of investment; (2) Increased knowledge and the existence of legal awareness in the management of traditional village-based Tourism Villages concerning land for investment purposes; (3) Able to develop the implementation of state law and customary law of Bali and tourism law to resolve the case of tourism investment in the traditional village of Anturan; (4) Can have a positive impact on society and can improve human resources, and the Kerta Desa in handling investment cases in tourism can apply the law in coexistence. The method used in the form of empowerment Kerta Desa with the pattern of assistance, FGD and find the real core of the problem. Legal issues are very complex, can find hidden problems in travel cases, and inventory problems and solve problems that arise with village officials, custom officers and indigenous community leaders in Anturan. Target outcomes to be achieved are publication of national journals / or proseding ISBN National publications, mass media publications, videos on broadcast activities. Activities in Empowering Anturan Indigenous Village Empowerment in resolving land issues in tourism investment by providing assistance and counseling to Kerta Desa, Prajuru Desa adat and community leaders who are relevant to Land Cases and investments in Anturan village.